The Application of Science and Technology in Law No. 28 of 2014 on Copyright for Lecturers at Universitas Muhammadiyah Papua - Herry M. Polontoh; Frans Reumi; Dudi Mulyadi; Tri Yanuaria; Ruth Kambuaya; Sobardo Hamonangan (PT. ALHAFI BERKAH INDONESIA, 2025)
The title of this community service activity is